Emotional and Psychological Safety in Healthcare Digitalization: A Design Ethnographic Study - Vöcking, Mara; Karrenbrock, Anne; Beckmann, Andreas; Vondeberg, Carmen; Obert, Laura; Hemming, Bernhard; Minartz, Peter; Bleck, Christian; Cürlis, Diana; Kuske, Silke (International Journal of Public Health, 2024)
Objectives: Emotional and psychological safety is important during the use of digital technologies in healthcare. We aimed to gain comprehensive insight into needs, influencing factors and outcomes in the context of perceived safety and digital technologies in healthcare. Methods: We employed a participatory, design ethnographic research approach with 16 participants in 10 use cases. The methods included in an iterative process were, think-aloud, guideline-based interviews, process mapping, storyboard creation, and photo documentation. A qualitative, primarily inductive data analysis and synthesis was performed. Results: Perceived safety is influenced by various factors and unmet needs. Increased perceived safety can positively support the use of digital technologies, whereas low perceived safety can limit or even hinder its use. Conclusions: The needs of the different target groups should be considered throughout the entire process of digital technology development and health care provision to support their implementation. These findings support further research by providing specific aspects of emotional and psychological safety regarding target groups, settings, and ages and those with different levels of affinity for digital technologies.